Highly ordered and periodic mesoporous Nafion membranes via colloidal silica mediated self-assembly for fuel cells - Li, J.; Tang, H.; Chen, L.; Chen, R.; Pan, M.; Jiang, San Ping (The Royal Society of Chemistry, 2013)
Highly ordered and periodic mesoporous Nafion membranes with controlled structural symmetries including 2D hexagonal, 3D face-centered, 3D cubic-bicontinuous and 3D body-centered have been successfully synthesized by a novel colloidal silica mediated self-assembly method with high proton conductivity particularly under conditions of low humidity.